1993
DOI: 10.1029/93jb01565
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of variations in faulting style at the Mid‐Atlantic Ridge

Abstract: Both volcanism and faulting contribute to the rugged topography that is created at the Mid‐Atlantic Ridge (MAR) and preserved off‐axis in Atlantic abyssal hill terrain. Distinguishing volcanic from fault‐generated topography is essential to understanding the variations in these processes and how these variations are affected by the three‐dimensional pattern of mantle upwelling, ridge segmentation, and offsets. Here we describe a new quantitative method for identifying fault‐generated topography in swath bathym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 61 publications
8
117
1
Order By: Relevance
“…Such a direct relation was shown by Shaw (1992) and Shaw and Lin (1993). They observed that large-throw, widely-spaced faults interpreted from multibeam bathymetry occur near segment ends where residual mantle Bouguer anomaly (RMBA) highs suggest thin crust.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Such a direct relation was shown by Shaw (1992) and Shaw and Lin (1993). They observed that large-throw, widely-spaced faults interpreted from multibeam bathymetry occur near segment ends where residual mantle Bouguer anomaly (RMBA) highs suggest thin crust.…”
Section: Discussionmentioning
confidence: 75%
“…However, the mechanism that transforms the steep relief of the inward-facing rift-valley wall into subsiding ridge-flank abyssal hills is poorly understood. Hypotheses include systematic development of normal faults dipping away from the ridge axis, reverse faulting, and/or progressive backtilting of fault blocks along existing inward-facing faults (e. g., Needham and Francheteau, 1974;Harrison and Stieltjes, 1977;Macdonald and Luyendyk, 1977;Macdonald and Atwater, 1978;Shaw and Lin, 1993). Although recent microseismicity studies suggest that faulting can occur up to 15 km off-axis (Wolfe et al, 1995), it is unclear how far off-axis faulting contributes to the formation of ridge topography.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal and spatial variations in the rate of magma accretion are frequently invoked to explain differences in faulting and axial morphology at slow-spreading ridges [29,35,36]. Regions with deep rift valleys are interpreted to reflect lower rates of magma injection, while shallower and more distributed rift morphology is taken to imply enhanced magmatism [13,37].…”
Section: Discussionmentioning
confidence: 99%
“…Near the segment center, the rift valley is typically shallow, formed by closely spaced faults with relatively small throw [6,35,44].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical models [e.g., Sparks et al, 1993] and observational geophysics [Kuo and Forsyth, 1988;Lin et al, 1990; Tolstoy et al, 1993] indicate that the least magmatic portions of slow spreading ridge segments are at segment ends where the ocean crust tends to be thin, the lithosphere is thick, and brittle deformation and fault throw are maximized [Shaw and Lin, 1993;Escartfn et al, 1997a]. Crustal morphology, gravity, and seafloor sampling also show that there is a consistent, strong asymmetry between inside-corner (IC) and outside-corner (OC) tectonic settings across the rift axis near segment ends [Tucholke and Lin, 1994].…”
Section: Geological Backgroundmentioning
confidence: 99%